2012
DOI: 10.1200/jco.2011.34.7898
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Susceptibility of Chronic Lymphocytic Leukemia to BCL2 Inhibition: Results of a Phase I Study of Navitoclax in Patients With Relapsed or Refractory Disease

Abstract: A B S T R A C TPurpose BCL2 overexpression is a hallmark of chronic lymphocytic leukemia (CLL). The novel BH3 mimetic navitoclax (ABT-263) specifically inhibits BCL2 and related proteins BCL-x L and BCL-w, potently inducing apoptosis of CLL cells in vitro. A phase I trial in patients with CLL was conducted to evaluate the safety, pharmacokinetics, and biologic activity of oral navitoclax. Patients and MethodsTwenty-nine patients with relapsed or refractory CLL received daily navitoclax for 14 days (10, 110, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
614
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 720 publications
(639 citation statements)
references
References 32 publications
(8 reference statements)
17
614
1
7
Order By: Relevance
“…The lack of a significant response to vorinostat or panobinostat alone (Figure 1b): (i) was consistent with the observed high levels of expression of BCL-2 in our CLL samples ( Figure 1c); (ii) was not due to inactivity of HDACi in the CLL cells since western blotting demonstrated a clear time-dependent increase in histone H3 acetylation following exposure to vorinostat ( Figure 1d); (iii) was consistent with our previous results for murine lymphoma cells overexpressing BCL-2. 1 As ABT-737 alone ( Figure 1e) exhibited a range in potency towards CLL comparable to reported results from others, 4 we surmised that the lack of synergy between the HDACi and ABT-737 may be due to a defect in the ability of HDACi to promote apoptotic signalling upstream of BCL-2.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The lack of a significant response to vorinostat or panobinostat alone (Figure 1b): (i) was consistent with the observed high levels of expression of BCL-2 in our CLL samples ( Figure 1c); (ii) was not due to inactivity of HDACi in the CLL cells since western blotting demonstrated a clear time-dependent increase in histone H3 acetylation following exposure to vorinostat ( Figure 1d); (iii) was consistent with our previous results for murine lymphoma cells overexpressing BCL-2. 1 As ABT-737 alone ( Figure 1e) exhibited a range in potency towards CLL comparable to reported results from others, 4 we surmised that the lack of synergy between the HDACi and ABT-737 may be due to a defect in the ability of HDACi to promote apoptotic signalling upstream of BCL-2.…”
supporting
confidence: 87%
“…The structural analogue ABT-263 (Navitoclax) is under clinical development and has shown encouraging single-agent activity in vivo. 1 Although single-agent efficacy has been demonstrated, responses were not complete. Thus, further therapeutic improvements remain necessary and outcomes for CLL patients may be improved by combination of ABT-737 with other agents, particularly those that activate the intrinsic apoptotic pathway.…”
mentioning
confidence: 99%
“…56 The clinical trial of ABT-263 in CLL demonstrated rapid and profound reduction of CLL cells in the blood, whilst bone marrow biopsies showed evidence of residual CLL cells. 26 In that study, resistance to ABT-263 correlated with higher Mcl-1 expression levels. 26 However, another study demonstrated that the resistance of CLL cells to ABT-737 was due to Bcl-2A1…”
Section: Discussionmentioning
confidence: 77%
“…24 The emergence of Bcl-2 inhibitors such as ABT-263 and ABT-199 are showing considerable promise for the treatment of CLL, however these drugs are unable to inhibit the antiapoptotic effects of Mcl-1 conferred by the microenvironment, 25 thus identifying a known mechanism of resistance to these BH3-mimetics. [26][27][28][29] Several pan-Bcl-2 family inhibitors such as obatoclax, sabutoclax and AT-101 have been developed with low micromolar potency against Mcl-1. Obatoclax (a BH-3 mimetic) has been investigated in a phase I clinical trial for advanced CLL, but its effect was limited.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we and others have recently discovered that the upregulation of the antiapoptotic Bcl‐2 family proteins is primarily responsible for the resistance of SCs to apoptosis, and Bcl‐2/xl/w inhibitors such as ABT‐263 are potent senolytic agents (Chang et al., 2016; Yosef et al., 2016; Zhu et al., 2016). Because long‐term treatment with a senolytic drug may be required to prevent/treat age‐related diseases and extend lifespan, there is a concern that Bcl‐2/xl/w inhibitors might be not safe for humans because of their known on‐target (thrombocytopenia) and off‐target toxicities (Roberts et al., 2011; Rudin et al., 2012; Vogler et al., 2011). Thus, it is important that we continue searching for novel senolytic targets to develop safer senolytic agents.…”
Section: Discussionmentioning
confidence: 99%